Time and literature - Allen, Thomas M., ed. (Cambridge Cambridge University Press, 2018)
Time and Literature features twenty essays on topics from aesthetics and narratology to globalisation and queer temporalities, and showcases how time studies, often referred to as 'the temporal turn', cut across and illuminate research in every field of literature, as well as interdisciplinary approaches drawing upon history, philosophy, anthropology, and the natural sciences. Part one, Origins, addresses fundamental issues that can be traced back to the beginnings of literary criticism. Part two, Developments, shows how thinking about Time has been crucial to various interpretive revolutions that have impacted literary theory. Part three, Application, illustrates the centrality of temporal theorising to literary criticism in a variety of contemporary approaches, from ecocriticism and new materialisms to media and archive studies. The first anthology to provide a synthesis of recent scholarship on the temporality of literary language from across different national and historical periods, Time and Literature will appeal to academic researchers and interested laypersons alike.
Keywords: Time in literature; Literature; Space and time